Effect of Prophylactic Medication on Associated Dizziness and Motion Sickness in Migraine. Issue 1 (January 2018) - Lee, Seung-Han; Jeong, Seong-Hae; Kim, Ji-Soo; Kim, Hyo-Jung; Choi, Kwang-Dong; Choi, Jae-Hwan; Oh, Sun-Young; Park, Ji-Yun; Kim, Dong Uk; Kim, Byung-Kun
Abstract : Objective: To determine the efficacy of prophylactic medications for migraine in reducing associated dizziness and motion sickness. Study Design: Multicenter prospective observational study. Setting: Nationwide 9 Dizziness Clinics in South Korea. Patients: One hundred thirty-eight patients who required a preventive medication for migraine accompanied by dizziness and motion sickness. Intervention: At least one of the prophylactic medications was prescribed among the beta-blockers, calcium channel blockers, tricyclic antidepressants, and antiepileptic drugs. Main Outcome Measure: For 3 months from the index visit, the patients had monthly assessments of the headache (frequency and duration), dizziness handicap inventory, University of California Los Angeles dizziness questionnaire, vertigo symptom scale, and motion sickness score. Results: The prophylactic medications significantly improved the headache profiles, all three parameters of dizziness (dizziness handicap inventory, University of California Los Angeles dizziness questionnaire, and vertigo symptom scale), and severity of motion sickness ( p < 0.001). Conclusion: The prophylactic medication for migraine also improves associated dizziness and motion sickness as well as the headaches. Abstract : Supplemental Digital Content is available in the text